Technology acceptance: Malaysian industrialised building system (IBS) case - Mohd Nawi, Mohd Nasrun; Mydin, Md Azree Othuman; Kamaruddeen, Ahmed Mohammed; Lee, Angela; Ibrahim, Siti Halipah (AENSI Publisher, 2015)
In embracing globalisation, it is necessary for all industries, including the AEC/FM industry, to be equipped with relevant technology.One such technology available for the sector is the industrialised building system (IBS).Since 1998, a substantial work of campaign in order to encourage the use of IBS in Malaysia has been done by Construction Industry Development Board (CIDB). For example providing large funds for research, creating standard through various training and promotional programmes. Previous studies have shown that using IBS can enhanced the management of project quality, automatically save cost and led to less rectification work of construction project. However, result revealed the adoption of IBS in Malaysia construction industry is still far from government desired. Disintegration among stakeholders during the design stage has been identified as one major barrier for implementing IBS. As such, this paper explores the potential solutions to reduce disintegration.The research presented uses focus groups to obtain qualitative data.It was found that increased collaboration and team integration, such as team accountability, structural organisation and operation in terms of work processes and environment will enhance the IBS adoption in the Malaysian construction industry.